Identification of Perceptions of Investment Tendency as a Response to Issue of Monkey Business to the University Students in Malang (Identifikasi Kecenderungan Persepsi Investasi sebagai Respon Isu Investasi Bodong pada Mahasiswa di Malang) - Daris Zunaida (Jurnal Pekommas, 2018)
Issues were the basis of perception forming because the developing issues gave the impact for any person’s perception. The negative issue of the fraud under the guise of investment certainly has a big impact on the formation of investment perception. University students were a receptive group of issues through intensive interaction by communication media so that they were quite a dynamic group formation of investment perception. This study aims to analyze the students’ gender tendency the formation of investment perception and to analyze the influence of negative issues toward the fraud under the guise of investment the formation of investment perception. The method used in the current research was the method on 318 students in Malang City. This current research was carried out when there were many negative issues surrounding the fraud underwrite of investment in 2017. The result showed that the investment perception is still low enough. The average score is 5.58 or 55.8% by maximum score. The average perception of female investment was higher than male, specifically is 57.7. The perception of male investment score was lower, is 5.36. It suggested that females were more interested in investment than male.Isu merupakan pangkal dari pembentukan persepsi karena seringkali isu yang berkembang berpengaruh pada persepsi seseorang. Isu negatif tentang penipuan berkedok investasi tentu saja akan berpengaruh besar pada pembentukan persepsi investasi. Mahasiswa merupakan kelompok yang mudah menerima isu lewat interaksi yang intensif dengan media komunikasi sehingga mahasiswa merupakan kelompok yang cukup dinamis dalam pembentukan persepsi investasi.Penelitian ini bertujuan untuk menganalisis kecenderungan gender mahasiswa dalam pembentukan persepsi investasi dan untuk menganalisis pengaruh isu negatif tentang penipuan berkedok investasi pada pembentukan persepsi investasi. Metode penelitian yang digunakan dalam penelitian ini adalah metode survei pada 318 orang mahasiswa diKkota Malang. Penelitian dilakukan saat terjadi banyak isu negatif seputar penipuan berkedok investasi pada 2017. Hasil penelitian menunjukkan bahwa persepsi investasi masih cukup rendah yaitu skor rata-ratan adalah 5, 58 atau 55,8 % dari skor maksimal. Rata-rata persepsi investasi perempuan lebih tinggi dari laki-laki yaitu 5,7. Skor persepsi investasi laki-laki lebih rendah yaitu sebesar 5,36. Hal ini menunjukkan bahwa perempuan lebih tertarik untuk melakukan investasi dibandingkan laki-laki.